Terrorism in Central African Republic: A Mosaic of State Fragility and Abnormality - Chukwuemeka N. Oko-Otu; Kelechi Johnmary Ani (Cogent Social Sciences, 2024)
Religious extremism and radicalization have dominated the discourse on the causes of terrorism. However, little is written of other drivers of terrorism, such as economic and social deprivations, which could prompt religious groups to resort to terrorism. Scholars have sufficiently analyzed the imports of radical ideological and religious views on the emergence of terrorist groups such as Al-Qaida, ISIS, Boko Haram, and Al-Shabaab. By contrast, the Seleka and anti-Balaka terrorists of the Central African Republic introduces a new perspective to the explanation of terrorism. This essay uses the analytical framework of abnormality and State fragility to discuss the rise of terrorism in the Central African Republic. The essay argues that the historical precedent of State failure and weak institutions provides a catalyst that propels the use of terrorism by religious groups, the state and organized groups to demand political and economic dividends as well as a tool for power contestations and regime change. The study recommends multiple peacebuilding and building nation-building processes that will aid the transformation of the state. They include the transformation of the subsistence farming culture to a masses-driven cash crop economy for exportation, which will manage state fragility and promote civil-military counter-terrorism culture at the grassroots.